Adapting crops for climate change: regaining lost abiotic stress tolerance in crops - Palmgren, Michael; Shabala, Sergey (Frontiers in Science, 2024)
It is often stated that agricultural outputs need to increase substantially to meet the demands for more food posed by a growing population. However, considering climate change, we argue that projected increases are unrealistic and that a more realistic goal would be to maintain yields per area of food production. This will require breeding for crops with increased tolerance to abiotic stresses such as drought, salinity, waterlogging and high temperatures. This goal can be accomplished in one of two ways: either by introduction of stress tolerance genes into present high yielding crops or, alternative, by increasing yields of already tolerant orphan crops and/or wild plants. We argue that the first strategy will require substantial improvements in cell-based phenotyping to identify stress tolerance genes available in the gene pool of the crop and its wild relatives and easing restrictions on the use of gene editing technologies. The success of the second strategy will depend on the number of domestications genes that need to be selected for in order to obtain yields comparable to present day cultivars. It is still too early to conclude which of the two strategies, rewilding (bringing genes lost from wild ancestors back to domesticated crops) or de novo domestication (domesticating resilient wild plants or underutilized crops directly), will be most effective for a future sustainable agriculture. However, given the importance of the issue, some rapid actions are needed in both spaces.